1998
DOI: 10.1111/j.1540-8191.1998.tb01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Improved Cerebral Function After Minimally lnvasive Bypass Surgery

Abstract: Cerebral dysfunction as evidenced by ASEM errors is common following coronary bypass on-pump, but rare with off-pump bypass surgery. Cerebral microemboli generated during CPB may account for this difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
34
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 12 publications
4
34
0
2
Order By: Relevance
“…Our results confirm recent studies that report a significant difference in MES observed in myocardial revascularization with and without CPB [12][13][14][15][16] . BhaskerRao and coworkers 12 compared neurologic outcome in 305 patients undergoing conventional CABG with CPB to 17 patients undergoing minimally invasive bypass surgery.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results confirm recent studies that report a significant difference in MES observed in myocardial revascularization with and without CPB [12][13][14][15][16] . BhaskerRao and coworkers 12 compared neurologic outcome in 305 patients undergoing conventional CABG with CPB to 17 patients undergoing minimally invasive bypass surgery.…”
Section: Discussionsupporting
confidence: 83%
“…BhaskerRao and coworkers 12 compared neurologic outcome in 305 patients undergoing conventional CABG with CPB to 17 patients undergoing minimally invasive bypass surgery. They found a significantly higher number of MES in the CPB group and suggested that this finding is associated with the lower scores in the neuropsychologic examination observed in this group.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Pathological examination by Moody et al 9 of the brain after conventional CABG revealed the presence of multiple emboli lodged in small cerebral arterioles and capillaries. Additionally, BhaskerRao et al 7 documented in a prospective study that cerebral dysfunction was significantly lower after CABG without cardiopulmonary bypass compared with on-pump CABG. Previous investigators have also found an association between prolonged cardiopulmonary bypass time (Ͼ120 minutes) and increased risk of postoperative stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers showed that even for a short period in which rSO 2 value would be under the level of 50%, this increases the duration of hospital stay, neurologic damage and impairment of cognitive functions significantly. [25][26][27] In a study regarding the use of NIRS, the patients were randomized during CABG and NIRS monitoring is applied to one group as double blind method and actively to the other group. It has been determined that the group to whom Active NIRS monitoring is applied and intervention is made as standardized, had less extended desaturations and shorter hospital stay durations and decreased vital organ mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%